Creative Thinking Ability of Vocational School Students in Contextual Trigonometry Learning Using Futsal - Adinda Sahira; Kiki Nia Sania Effendi; Rika Mulyati Mustika Sari (Journal of General Education and Humanities, 2026)
This study explores the limited use of contextual approaches in fostering creative thinking in trigonometry learning. This study aims to determine the difference in creative thinking test scores of vocational high school students before and after learning trigonometry in the context of futsal. This study used a quantitative method with a pre-experimental design and a one-group pretest-posttest form, with 27 tenth-grade students as the sample. The instrument used was a mathematical creative thinking ability test with futsal-contexted trigonometry material. Data analysis included descriptive statistics, the Shapiro-Wilk normality test, the Wilcoxon test, and N-Gain. Descriptive results showed that creative thinking ability was in the moderate range (63%) and increased from 41.81 to 77.26 between the pretest and posttest. The Wilcoxon test showed that Ho was rejected and Ha accepted, indicating a difference in creative thinking skills before and after the treatment (0.000 < 0.05), with an N-Gain score of 0.77. Therefore, it was concluded that the futsal sports context in trigonometry material yielded good results, with a noticeable difference before and after classroom learning.